Influencing Factors on the Success of Mobile Learning: A Systematic Review and Meta-Analysis - Mehrfar, Abdollah; Zolfaghari, Zahra; Bordbar, Arash; Mohabbat, Zahra (Investigación y Educación en Enfermería, 2024)
Objective. To study the geographical regions, success factors, and types of mobile device features that could result in educational success and early take-up. Methods. This systematic review and meta-analysis searched PubMed, CINAHL, EMBASE, PsycINFO and ProQuest databases between 2010 and November 2022. The keywords were m-learning features, practical experiences, and influencing. Comprehensive Meta-Analysis software was used to analyze and combine data. Results. 48 articles were reviewed in this study. Compatibility and user-friendliness of mobile phones were mentioned as key factors influencing the use of mobile devices in learning. Also, the key role of users’ perspectives, attitudes, and skills as determinant factors of applying mobile technology in the learning process was revealed, which confirms its significant role in the success of m-Learning. Other influencing factors were tools readiness, the availability of appropriate resources, motivation of learners and their active engagement, support, and learning styles which considerably could play a key role in improving the quality of m-learning. Applying different strategies including collaboration, effective interaction, reflection, or inquiry-based learning can be beneficial in improving the success rate of m-learning. The final factor was technical competence which showed a significantly negative correlation with m-learning success according to learners’ perspective. The meta-analysis indicated that most studies on mobile learning were conducted between 2015 and 2021, primarily utilizing quantitative methodologies. These studies focused on young adults and were carried out in various countries, including the United States, Spain, Taiwan, Saudi Arabia, the United Kingdom, Turkey, China, Australia, Italy, Sri Lanka, Malaysia, Oman, Austria, South Africa, Egypt, India, Portugal, Jordan, South Korea, Iran, Finland, Brazil, and Israel. A meta-analysis identified 23 countries, with the United States having the highest number of studies on mobile learning success factors. Key determinants reported were learning approach and learners’ perception, with estimates of 0.68 (95% CI 0.06-0.98) and 0.44 (95% CI 0.33-0.56), respectively. In contrast, Jordan and Iran had the lowest number of studies, with learning approach being the main contributing success factor from the learners’ perspective, estimated at 0.736 (95% CI 0.68-0.78) Conclusion. Successful m-learning should include the investigation of trainees’ educational needs and motivation; provision of adequate infrastructure and learning materials; definition of learning objectives and course contents; and coordination of appropriate learning activities in order to ensure continuous progress in learners’ knowledge and awareness on different course topics.